Prevalence of Viral (HBV, HCV & HIV) Co-infections among Apparently Healthy Blood Donors in Jharkhand India - Sushma, Kumari; Asha, Kiran; Ritesh, Kumar; Shrivastava, R. K. (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Apparently healthy blood donors might carry double viral co-infections that might be more fatal than viral mono-infection for the donors themselves as well as recipients later on. The aim of this study is to assess the seroprevalence of double viral co-infections among apparently healthy blood donors in, Jharkhand India. This is a retrospective study done at Blood Centre, RIMS, Ranchi from 17th July 2015 to 16th January 2017 (18 months study). All blood samples were screened for HIV-I and II (4th generation kit), HBV and HCV (3rd generation kit) by using chemiluminescence techanique (Manufacturer –Abbott, Model-Architect i 1000SR). The findings of this study shows that On screening of 41307 blood units, 829 (2.0%) donors were found positive for one of the viral infection (HBV,HCV& HIV). Highest prevalence was for HBV ( 417 donors -1.0%) followed by HCV(324 donors -0.78 %) and HIV (88 donors -0.21 %). 08 (0.019%) donors showed double viral co-infection. 05 (0.012%) donors showed double viral co-infection with HBV and HCV while 03 (0.0072%) donors showed double viral co-infection with HBV and HIV. Blood donors who appear to be healthy could be carrying life-threatening double virus co-infections.